ВЛИЈАНИЕТО НА ДЕЛОТО „ЗА ОЗНАКИТЕ“ ОД ЏУЛИО ЧЕЗАРЕ КАРПАЧО НА ИЛИРСКАТА ХЕРАЛДИКА И МАКЕДОНСКИОТ ЗЕМСКИ ГРБ / THE INFLUENCE OF JULIO CESARE CARPACCIO’S DELLE IMPRESE ON ILLYRIAN HERALDRY AND THE MACEDONIAN LAND COAT OF ARMS - Ivan Nacevski (Македонски хералд - Macedonian Herald, 2019)
Julio Cesare Capaccio is an Italianliterary, theologian, historian and poetfrom the Kingdom of Naples. In 1592, inNaples, under his authorship, the workDelle imprese, or On the Insignias, waspublished. It is a heraldic work of the Ordinariumtype. It depicts various coat ofarms through blazons and emblazoned onmany different coats of arms. Julio CesareCapaccio’s Delle imprese has a significantinfluence on the creation of the Korenic-NeoricArmorial, and thus the entire Illyrian heraldry. Theappearance of the lion in the Macedonian Arms ofthe Illyrian Armorial inevitably raises the questionof its origin and its relation to the lion from the attributedArms of Alexander the Great.